Virtual laboratory for understanding impact of heterogeneity on ecohydrologic processes across scales. (March 2022) - Wang, Kunxuan; Kumar, Praveen
Abstract: Hyper-resolution land surface models can explicitly represent landscape scale heterogeneity, but the complexity of representing finer scale processes and meeting computational needs makes them inaccessible to the general scientific community and limits their adoption. In this work, we present the Multi-layer Canopy and 3D Soil (MLCan3D) model, which is a high resolution, high fidelity, physical ecohydrologic model that aims to maintain accessibility. MLCan3D implements detailed physical process representations, is accessible through graphical user interface, and is tested using comparisons with other models and field data. This work demonstrates the feasibility of using MLCan3D to produce simulations close to real systems and the potential of the model to perform virtual experiments to explore model results. Our goal is for MLCan3D to serve as a virtual laboratory that enables virtual experiments from the broader scientific community and contribute to our understanding of ecohydrologic process heterogeneity, dynamics, and interactions across scales. Highlights: We couple 1D ecohydrologic process model with new topography aware 3D flow model. Model includes 2D diffusive overland and 3D Richards' equation subsurface flow. The 3D terrain-following Richards' equation is solved using the AIADI method. A graphical user interface (GUI) is provided to initialize and run the model. Model is applied to sites from NEON and results are comparable with field data.